Maritime History at the Crossroads : a Critical Review of Recent Historiography. - Broeze, Frank (Oxford : Liverpool University Press, 2017)
This volume seeks to critically review the contemporary state of maritime historiography, as it stands at the volume's publication date of 1995.
Recent Developments in the Historiography of Maritime History in the NetherlandsThe Ottoman Empire: Recent Research on Shipping and Shipbuilding in the Sixteenth to Nineteenth Centuries; The Progress of Maritime History in Spain since 1975; Oceanic Historiography: The American Dimension; The Historians and Maritime Labour, c. 1850-1930.
Print version record.
JSTOR
Keywords: Merchant marine -- Historiography; Navigation -- History -- Historiography; Navigation -- History; Marine marchande -- Historiographie; Navigation -- Histoire; History